Storage Artifact Masquerading as Yeast: Presenting a Diagnostic Pitfall - Elena M. Fenu; Tawfeq Naal; Elizabeth Palavecino (Case Reports in Pathology)
Abnormal cell morphology can result from prolonged specimen storage, both for red and white blood cells. In particular, nuclear pyknosis of segmented neutrophils can occur in both peripheral blood and body fluids and may represent a diagnostic pitfall as it can mimic intracellular yeast or bacteria morphology. Pathologists are frequently asked to examine body fluid smears which are thought to contain microorganisms, and the presence of an unexpected organism can be especially concerning. Morphologic changes from prolonged storage may be encountered infrequently, and it is important to be aware of them in order to avoid misrepresentation, as additional work-up may be required for a suspected case of an unexpected fungal infection.